ANALISIS RASIONALISASI KEPUTUSAN AMERIKA SERIKAT DALAM MELAKSANAKAN INDIRECT APPROACH PADA OPERATION ENDURING FREEDOM – PHILIPPINES PADA TAHUN 2002-2015 - Negoro, Abimanyu Kusumo; Priadarsini, Ni Wayan Rainy; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2022)
This study aims to analyze the rationalization behind the decision to implement an indirect approach in dealing with the problem of terrorism in the Philippines by the United States. The policy, which was later referred to as Operation Enduring Freedom, is an operation to deal with the threat of terrorism by the Abu Sayyaf Group which is connected to the global terror network after the 911 attack which was carried out with an indirect approach through military-civilian operations, economic assistance, educational assistance, health assistance, and infrastructure assistance to hinder the operations of the Abu Sayyaf Group. This study uses an explanatory qualitative method with data collected through literature study. The conceptual framework used in this research is the concept of rational actor. The results of this study are an overview of the process of rationalizing the steps taken by the United States. Keywords: United States, Philippines, Operation Enduring Freedom, Rational Actor Model